La musica nella crisi identitaria del mondo islamico - Tieri, Francesco (Occhialì, 2019)
The music historically produced in the Islamic countries is for all intents and purposes oriental music and, as any cultural aspect of the East, suffers at present from the identity crisis stemming from the westernization process. This crisis, which for over two centuries has coincided with the decline of the Islamic civilization and with the consolidation of Western hegemony in all domains of cultural production, has entailed in the musical field the stagnation of historical traditions and the adoption of imported musical forms. Our aim through this contribution is to analyze some aspects of the musical dimension in the Islamic world, during the latest phase of its evolution, with reference to a few geographical areas.